Problems of anti-tuberculosis therapy in patients on hemodialysis - O. M. Gordeeva; A. M. Tikhonov; S. N. Andreevskaya; E. E. Larionova; N. L. Karpina (Туберкулез и болезни лёгких)
The objective: to determine possibility of prescribing and safety of various anti-tuberculosis drugs and their combinations as part of a therapeutic or preventive course of anti-tuberculosis therapy (ATBT) in patients with end-stage chronic kidney disease (CKD) receiving hemodialysis replacement therapy in the settings with high prevalence of drug resistant strains of Mycobacterium tuberculosis.Subjects and Methods. 42 patients receiving hemodialysis replacement therapy were followed-up by Central Tuberculosis Research Institute: of them, 31 (73.8%) had active tuberculosis and 11 (26.2%) had residual post-tuberculous changes in the respiratory organs. During the follow-up, the nature and severity of adverse reactions to anti-tuberculosis drugs were assessed.Results. In the patients with end-stage CKD suﬀering from respiratory tuberculosis, drug resistant strains prevailed – 68.2%. Some of adverse events developed when taking anti-tuberculosis drugs were as follows: deterioration of uremia in 20.5% of cases, cardiovascular complications – in 17.9%, and neurotoxic reactions – in 15.4%. Progression of uremia occurred more often in the followed-up patients taking anti-tuberculosis drugs versus hepatotoxic reactions (p = 0.02). When treating tuberculosis patients with end-stage CKD, isoniazid was discontinued due to adverse events in 12.8% of cases and pyrazinamide in 12.8% of cases, other drugs were discontinued less frequently. Compilation of individual regimens of anti-tuberculosis drugs with the consideration of drug susceptibility testing results, contraindications, and concomitant diseases made it possible to provide an adequate anti-tuberculosis therapy for patients with end-stage CKD with tuberculosis infection in 92.9% of cases for a period of more than 6 months.